Electronic and Spectroscopic Properties of Some Carbamate Derivatives as Chelating Ligands for Removing Ni2+ Ions from Biological Systems - Sheikhshoaie, Iran; Jamilladdin Fatemi, S. (Asian Journal of Chemistry, 2010)
The interactions of some carbamate derivatives, such as diethylcarbamate, dithiooxamide and ammonium N,N´-tetramethylene dithiocarbamate with Ni2+ have been studied in our laboratory. In the present study, by some semi-empirical calculations, we have investigated the electronic properties and also the electronic spectra of the above carbamate compounds in order to provide better understanding about the behaviour of these compounds for binding to Ni2+. The mentioned compounds have potential coordination sites for binding to the metal ions; so these compounds are good chelating agents for removing Ni2+ from biological systems.